Efficient N-arylation of amines catalyzed by Cu-Fe-hydrotalcite - Jadhav, Vinod H.; Dumbre, Deepa K.; Phapale, Vilas B.; Borate, Hanumant B.; Wakharkar, Radhika D. (Catalysis Communications, 2007)
An efficient N-arylation of amines with aryl halides in presence of heterogeneous recyclable Cu-Fe-hydrotalcite catalyst has been developed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: amines; Aryl halides; Cu-Fe-hydrotalcite; heterogeneous catalyst; N-arylation

Synthesis of substituted styrenes and stilbenes mediated by palladium on zirconia - Borate, Hanumant B.; Dumbre, Deepa K.; Wakharkar, Radhika D.; Choudhary, Vasant R. (Journal of Chemical Research-S, 2008)
Palladium on zirconia has been found to be an effective catalyst for the synthesis of various substituted styrenes and stilbenes, including biologically active natural products, by reaction of aryl halides with olefins.
Keywords: heterogeneous catalyst; palladium on zirconia; stilbenes; styrenes

Magnesium oxide supported nano-gold: a highly active catalyst for solvent-free oxidation of benzyl alcohol to benzaldehyde by TBHP - Choudhary, Vasant R.; Dumbre, Deepa K. (Catalysis Communications, 2009)
Nano-size gold particles deposited on MgO by the homogeneous deposition- precipitation showed very high catalytic activity with nearly 100% conversion of benzyl alcohol in a short reaction period (0.5 h) and more over showed excellent reusability in the process. Influence of the catalyst support (MgO, CaO, BaO, SrO, Al(2)O(3), Ga(2)O(3) and In(2)O(3)), method of gold deposition, Au loading and catalyst calcination temperature and also that of the reaction conditions (viz. reaction time and temperature) on the benzyl alcohol to benzaldehyde oxidation have been thoroughly investigated. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Alkaline earth oxides; Benzaldehyde; Benzyl alcohol; Gr.IIIa metal oxides; Oxidation

Oxidation of benzyl alcohol to benzaldehyde by tert-butyl hydroperoxide over nanogold supported on TiO2 and other transition and rare-earth metal oxides - Choudhary, Vasant R.; Dumbre, Deepa K.; Bhargava, Suresh Kumar (Industrial & Engineering Chemistry Research, 2009)
Liquid-phase oxidation of benzyl alcohol to benzaldehyde by tertiary butyl hydroperoxide (at 95 degrees C) over nanogold supported oil TiO2 and other transition-metal oxides (viz, MnO2, Fe2O3, CoOx, NiO, CuO, ZnO, and ZrO2) or rare-earth oxides (viz, La2O3, Sm2O3, Eu2O3, and Yb2O3) by the homogeneous deposition-precipitation (HDP) method has been investigated. The Au/TiO2 catalyst, prepared using the HDP method, showed high activity and selectivity in the reaction. The ZrO2-Supported nanogold catalyst (HDP) also showed very good performance. The Au/TiO2 catalyst that was prepared using the deposition-precipitation (DP) method, however, showed poor catalytic activity, mostly because of its much-lower gold loading and/or lower Au3+/Au-0 ratio. Irrespective of the catalyst preparation method, the catalytic activity increased as the gold loading increased. The gold deposition method strongly influenced the amount of gold that was deposited on TiO2, the gold particle size distribution, and also the surface Au3+/Au-0 ratio; using the HDP method, the gold deposition was much larger, the gold particle size was smaller, the gold particle size distribution was much narrower, and the Au3+/Au-0 ratio was higher. Both the metallic and ionic gold species (Au-0 and Au3+) are present in the Au/TiO2 catalyst. However, the Au3+ species are mostly responsible for the high catalytic activity in the oxidation process.

Supported nano-gold catalysts for epoxidation of styrene and oxidation of benzyl alcohol to benzaldehyde - Choudhary, Vasant R.; Dumbre, Deepa K. (Topics in Catalysis, 2009)
Nano-gold particles supported on different alkaline earth oxides (viz. MgO, CaO, BaO and SrO), Gr. IIIa metal oxides (viz. Al(2)O(3), Ga(2)O(3), In(2)O(3) and Tl(2)O(3)), transition metal oxides (viz. TiO(2), Cr(2)O(3), MnO(2), Fe(2)O(3), CoO(x), NiO, CuO, ZnO, Y(2)O(3) and ZrO(2)), rare earth metal oxides (viz. La(2)O(3), Ce(2)O(3), Nd(2)O(3), Sm(2)O(3), Eu(2)O(3), Tb(2)O(3), Er(2)O(3) and Yb(2)O(3)) and U(3)O(8) [all prepared by depositing gold on corresponding metal oxide support by deposition precipitation (DP) and/or homogeneous deposition precipitation (HDP) method] were evaluated for their catalytic performance in the liquid phase epoxidation of styrene by tert-butyl hydroperoxide (TBHP) to styrene oxide and also in the solvent-free benzyl alcohol-to-benzaldehyde oxidation (by molecular oxygen or TBHP) reactions. For the epoxidation, the catalytic performance (styrene oxide yield) of the most promising nano-gold catalysts prepared by the HDP method was in the following order: Au/MgO > Au/Tl(2)O(3) > Au/Yb(2)O(3) > Au/Tb(2)O(3) > Au/CaO (or TiO(2)). However, for the oxidation of benzyl alcohol to benzaldehyde by molecular oxygen, the order of choice for the most promising catalysts (based on benzaldehyde yield) was Au/U(3)O(8) > Au/Al(2)O(3) > Au/ZrO(2) > Au/MgO. Whereas, when TBHP was used as an oxidizing agent for the benzyl alcohol oxidation, the order of choice for the most promising catalysts was Au/U(3)O(8) > Au/MgO > Au/TiO(2) > Au/ZrO(2) > Au/Al(2)O(3). The catalytic performance of a particular supported nano-gold catalyst was thus found to depend on the reaction catalysed by them. Moreover, it is strongly influenced by a number of catalyst parameters, such as the metal oxide support, the method of gold depositon on the support, the gold loading and also on the catalyst calcination temperature. Nano-gold particles-support interactions seem to play an important role in controlling the deposition of gold ( amount of gold deposited and size and morphology of gold particles), formation of different surface gold species (Au(0), Au(1+) and Au(3+)) and electronic properties of gold particles and, consequently, control the catalytic performance (both the activity and selectivity) of the supported nano-gold catalysts in the reactions. The nano-gold catalysts prepared by the HDP method showed much better catalytic performance than those prepared by the DP, coprecipitation or impregnation method; in general, the HDP method provided supported gold catalysts with much higher gold loading and/or smaller size gold particles than that achieved by the DP and other methods.
Keywords: Benzaldehyde; Benzyl alcohol; epoxidation; Metal oxide supports; Nano-gold catalysts; Oxidation; styrene; Styrene oxide

Solvent-free selective oxidation of benzyl alcohol to benzaldehyde by tert-butyl hydroperoxide over U3O8-supported nano-gold catalysts - Choudhary, Vasant R.; Dumbre, Deepa K. (Applied Catalysis A-General, 2010)
Liquid-phase oxidation of benzyl alcohol to benzaldehyde by tertiary butyl hydroperoxide over different uranium oxide supported nano-gold catalysts in the absence of a solvent has been thoroughly investigated. The influences of catalyst parameters [viz, method of gold deposition (impregnation, co-precipitation, deposition-precipitation and homogeneous deposition-precipitation), gold loading (08 wt%) and catalyst calcination temperature (100-900 degrees C)] on the catalyst performance have been investigated. The influence of reaction conditions [viz, reaction time (0-2 h) and temperature (25-94 degrees C)] on the process performance has also been studied. The Au/U3O8 catalyst prepared by the homogeneous deposition-precipitation and calcined at 400 degrees C showed very high activity (100% benzyl alcohol conversion with >85% selectivity for benzaldehyde) in the process for a short reaction period (0.5 h) at 94 degrees C. The catalyst also showed excellent reusability in the process. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Au/U3O8 catalyst; Benzaldehyde; Benzyl alcohol; Nano-gold; Partial oxidation; tert-Butyl hydroperoxide

Greener ullmann-type coupling of aryl halides for preparing biaryls using reusable Pd/ZrO2 catalyst - Dumbre, Deepa K.; Wakharkar, Radhika D.; Choudhary, Vasant R. (Synthetic Communications, 2011)
Biaryls with excellent yields can be prepared by the Ullmann-type coupling of aryl halides in the presence of potassium carbonate (as a base) and dimethylformamide (as a solvent), at 140 degrees C, using a reusable Pd (2.5wt%)/ZrO2 catalyst. The product yield of 4-iodoanisole coupling is strongly influenced by the catalyst preparation method, solvent, and base.
Keywords: Aryl halides; Biaryls; Pd; Ullmann coupling reaction; ZrO2

One-pot three-component kabachnik-fields synthesis of alpha-aminophosphonates using H-beta zeolite catalyst - Tillu, V. H.; Dumbre, Deepa K.; Wakharkar, R. D.; Choudhary, Vasant R. (Tetrahedron Letters, 2011)
One-pot three-component Kabachnik-Fields synthesis of alpha-aminophosphonates with high yields from the reaction between carbonyl compound, primary amine, and substituted phosphite can be carried out in a short period, using H-beta zeolite as a reusable catalyst. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Carbonyl compound; H-beta zeolite; Primary amine; Substituted phosphite

Solvent-free selective oxidation of primary alcohols-to-aldehydes and aldehydes-to-carboxylic acids by molecular oxygen over MgO-supported nano-gold catalyst - Choudhary, Vasant R.; Dumbre, Deepa K. (Catalysis Communications, 2011)
Magnesium oxide supported nano-gold catalyst (prepared by the homogeneous deposition precipitation technique) showed high activity/selectivity and excellent reusability in the oxidation of different primary alcohols and aldehydes to corresponding aldehydes and carboxylic acids, respectively, by molecular oxygen (under atmospheric pressure) in the absence of any solvent. Influence of the catalyst calcination temperature (400-900 degrees C), reaction temperature (50-120 degrees C) and use of different solvents (viz. toluene. p-xylene, DMF or DMSO) on the oxidation reaction has also been studied. (C) 2011 Published by Elsevier B.V.
Keywords: Alcohols; aldehydes; Au/MgO; Molecular oxygen; Solvent-free oxidation

Thermally decomposed Ni-Fe-hydrotalcite: a highly active catalyst for the solvent-free N-acylation of different amines by acid chlorides - Choudhary, Vasant R.; Dumbre, Deepa K. (Catalysis Communications, 2011)
A composite Ni-Fe catalyst obtained from the thermal decomposition of Ni-Fe-hydrotalcite at 600 degrees C shows very high activity in the solvent-free N-acylation of amines by different acid chlorides with high product yields under very mild reaction conditions (viz, room temperature, short reaction period and small amount of catalyst). The catalyst also shows excellent reusability in the reaction. The crystalline phases present in the catalyst are mixed oxides and hydroxides of nickel and iron. The high catalytic activity of the decomposed Ni-Fe-hydrotalcite is attributed to the formation of uniformly distributed Ni-Fe metal oxides and hydroxides. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Acid chlorides; amines; Decomposition of Ni-Fe-hydrotalcite; N-acylation of amines; Ni-Fe-hydrotalcite derived catalyst

FeCl3/Montmorillonite K10 as an efficient catalyst for solvent-free aza-Michael reaction between amine and alpha,beta-unsaturated compounds - Choudhary, Vasant R.; Dumbre, Deepa K.; Patil, S. K. (RSC Advances, 2012)
A highly efficient, inexpensive and greener protocol for aza-Michael addition reaction of different aromatic and aliphatic/cyclic amines to alpha,beta-unsaturated compounds using a FeCl3/MontK10 catalyst under solvent-free conditions has been developed. The Michael addition products are obtained in good to excellent yields. The catalyst was insensitive to moisture and it also showed excellent reusability in the reaction. Its high activity is attributed mostly to redox properties of FeCl3.

Solvent-free one-pot synthesis of sulfonephthaleins from saccharin and phenols - Tillu, V. H.; Dumbre, Deepa K.; Borate, Hanumant B.; Wakharkar, R. D.; Choudhary, Vasant R. (Synthetic Communications, 2012)
Sulfonephthaleins can be synthesized in a single pot from saccharin and phenol via the in situ formation of 2-sulfobenzoic anhydride, followed by its reaction with phenol using H2SO4 as the condensing agent, in the absence of any solvent. This solvent-free synthesis is more economical and environmentally benign.
Keywords: H2SO4; Phenols; saccharin; sulfonephthalein

Solvent-free oxidation of aldehydes to acids by TBHP using environmental-friendly -exchanged Mg-Al hydrotalcite catalyst - Choudhary, Vasant R.; Dumbre, Deepa K.; Narkhede, Vijay S. (Journal of Chemical Sciences, 2012)
A number of hydrotalcite (Mg-Al, Mn-Al, Co-Al, Ni-Al, Mg-Fe, Mg-Cr and Cu-Al) catalysts, with or without MnO-exchange, were evaluated for their performance in the solvent-free oxidation of benzaldehyde to benzoic acid by tert-butyl hydroperoxide under reflux in the absence of any solvent. The MnO-exchanged Mg-Al-hydrotalcite (Mg/Al = 10) showed high activity in the oxidation of different aromatic and aliphatic aldehydes to their corresponding acids and also showed excellent reusability in the oxidation process which is environmental-friendly.
Keywords: acid; Aldehyde; MnO4-1-exchanged Mg-Al-hydrotalcite catalyst; Oxidation; TBHP

Thermally decomposed Cu-Fe-hydrotalcite. a novel highly active catalyst for o-arylation of naphthol and phenols by aryl halides - Choudhary, Vasant R.; Dumbre, Deepa K.; Yadav, P. N.; Bhargava, Suresh Kumar (Catalysis Communications, 2012)
A novel, efficient and environmentally benign method has been reported for the synthesis of diaryl ethers by the o-arylation of napthol or phenols with aryl halides in dimethylformamide (as a solvent) under reflux, using a novel heterogeneous catalyst (having redox properties), obtained from thermal decomposition of Cu-Fe at 600 degrees C in the absence of externally added base. The catalyst comprises Cu(II) and Fe(III) species (oxides and hydroxides), which are uniformly distributed during the catalyst formation. The catalyst can be easily separated from the reaction mixture, simply by filtration and reused several times without a significant loss of its activity. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Aryl halides; C-O cross coupling reaction; Cu-Fe-hydrotalcite; Naphthol; o-Arylation; Phenols

Epoxidation of styrene by t-butyl hydroperoxide over gold nanoparticles supported on Yb2O3: effect of gold deposition method, gold loading, and calcination temperature of the catalyst on its surface properties and catalytic performance - Choudhary, Vasant R.; Dumbre, Deepa K.; Patil, N. S.; Uphade, B. S.; Bhargava, Suresh Kumar (Journal of Catalysis, 2013)
Surface properties and epoxidation performance of Au/Yb2O3 catalyst are influenced by the method of gold deposition [viz. deposition-precipitation (DP), homogeneous deposition-precipitation (HDP) or impregnation], gold loading (0.9-6.6 wt%), and the catalyst calcination temperature (400-900 degrees C)]. The catalyst showed the best epoxidation performance when it was prepared by the HDP method and calcined at 500 degrees C. The Au/Yb2O3 catalyst even after calcination at 900 degrees C showed good activity and epoxide selectivity. Both Au-0 and Au3+ surface species were found in the catalyst calcined at 800 degrees C, but only Au-0 species were observed at the lower calcination temperatures (<600 degrees C). The selectivity for styrene oxide increased continuously with the reaction temperature (from 75 degrees C to 97 degrees C) and time (1-5 h), indicating that styrene oxide did not undergo secondary reactions under these conditions. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Au/Yb2O3 catalyst; Epoxidation of styrene; gold nanoparticles; Styrene oxide; tert-Butyl hydroperoxide

Suzuki-Miyaura cross-coupling reaction between aryl halides and phenylboronic acids over gold nano-particles supported on MgO (or CaO) and other metal oxides - Dumbre, Deepa K.; Yadav, P. N.; Bhargava, Suresh Kumar; Choudhary, Vasant R. (Journal of Catalysis, 2013)
Gold nano-particles-supported alkaline earth metal oxides, particularly MgO or CaO, show high catalytic activity in the Suzuki-Miyaura cross-coupling reaction in the presence of K2CO3 and DMF (as a solvent). The catalytic activity is strongly influenced by the nature or type of metal oxide support (viz, alkaline earth oxide, Group IIIA metal oxide, transition metal oxide, or rare earth oxide actinide oxide). It is also strongly influenced by the nature of aryl halide (aryl iodide, bromide, chloride, or fluoride), amount of K2CO3 in the reaction mixture and catalyst calcination temperature. Influence of reaction parameters viz, temperature and time and different substituents in aryl halides and/or phenylboronic acids on the biphenyl product yield in the reaction over Au/MgO catalyst has also been investigated. The catalyst showed excellent reusability in the reaction. Moreover, it is ligand-free and also has much lower cost than the commonly used homogeneous and heterogeneous Pd catalysts. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Aryl halides; Au/MgO (or CaO) catalyst; Biphenyls; Gold nano-particles; phenylboronic acids; Suzuki-Miyaura coupling reaction

Calcium oxide supported gold nanoparticles as catalysts for the selective epoxidation of styrene by t-butyl hydroperoxide - Dumbre, Deepa K.; Choudhary, Vasant R.; Patil, Nilesh S.; Uphade, Balu S.; Bhargava, Suresh Kumar (Journal of Colloid and Interface Science, 2014)
Gold nanoparticles are deposited on basic CaO supports as catalysts for the selective conversion of styrene into styrene oxide. Synthetic methods, gold loading and calcination temperatures are varied to permit an understanding of their influence on gold nanoparticle size, the presence of cationic gold species and the nature of interaction between the gold nanoparticles and the CaO support. Based on these studies, optimal conditions are designed to make the Au/CaO catalyst efficient for the selective epoxidation of styrene. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Au/CaO; Epoxidation of styrene; gold nanoparticles; Homogenous deposition precipitation method; Styrene oxide

Mesoporous, ligand free Cu-Fe solid catalyst mediated CS cross coupling of thiols with aryl halides - Dumbre, Deepa K.; Selvakannan, P. R.; Patil, S. K.; Choudhary, Vasant R.; Bhargava, Suresh Kumar (Applied Catalysis A-General, 2014)
Solid catalyst derived from Cu-Fe hydrotalcite was demonstrated to be a novel, ligandless, efficient and environmentally greener catalyst for the synthesis of diaryl sulfurs from the C-S cross coupling reaction of substituted thiols with different aryl halides. This catalyst has shown higher product yield in the presence of dimethylformamide (as a solvent) and K2CO3 (as a base) at 120 C. Influence of different solvents and bases on the product yield has also been investigated. The catalyst can be easily separated from the reaction mixture, simply by filtration and reused several times without a significant loss of its activity. The catalyst has been fully characterized for its surface and bulk properties and the mesoporous CuO:Fe2O3 phase was attributed for its catalytic activity towards S-arylation reactions. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: C-S cross coupling; Cu-Fe-hydrotalcite; S-arylation

Studies of synergy between metal-support interfaces and selective hydrogenation of HMF to DMF in water - Goyal, Reena; Sarkar, Bipul; Bag, Arijit; Siddiqui, Nazia; Dumbre, Deepa K.; Lucas, Nishita; Bhargava, Suresh Kumar; Bordoloi, Ankur (Journal of Catalysis, 2016)
Metal-support interfaces play a very important role in heterogeneous catalysis. The interfacial interactions not only are responsible for stabilizing the necessary oxidation state to facilitate the reaction but also enhance the stability of the catalyst system. Nano dispersion of Ni on mesoporous nitrogen-rich carbon material has been achieved using two different synthesis methods. It was observed that nickel (0) gets stabilized by strong interfacial interaction with the nitrogen atoms of the support material, and the material was found to be very economic and efficient for the conversion of HMF to DMF in aqueous medium. The material shows >= 99% conversion to 5-(hydroxymethyl) furfural (HMF) within 6 h of reaction with 98.7% DMF selectivity. A unique correlation between synthesis methods and particle sizes with catalytic performance has been observed for these newly developed materials. Furthermore, a DFT calculation has been performed to predict the reaction mechanism. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: biofuels; Biomass; Hydrogenation; mesoporous carbon; Ni-CNx